Understanding driving-related fear : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Psychology at Massey University - Taylor, Joanne Elizabeth (Massey University, 2002)
Driving-related fear (DRF) has been investigated predominantly through research on the psychological consequences of motor vehicle accidents. There is a small but growing literature documenting the characteristics of DRF within a broader population. These few studies have described DRF as diagnostically complex and difficult to characterise in terms of clear anxiety disorders. Particularly problematic is the frequent presence of many different foci of fear and fear cognitions that are typically used to distinguish the various anxiety disorders. In addition, driving skills in those who report DRF has been a neglected issue in previous studies. The central aim of the present study was to conduct a comprehensive examination of the clinical characteristics of those who report DRF. Such an investigation would help to generate a clearer understanding of the nature of DRF and subsequently inform approaches to assessment and treatment. The present research comprised two separate studies. Study One aimed to ascertain the need for more comprehensive research by comparing the characteristics of drivers who were fearful as a result of a motor vehicle accident (MVA) with those who developed their DRF through other means. Participants were 85 media-recruited volunteers who reported some degree of DRF. Questionnaire data provided information on the types of concerns and expectations while driving, as well as various measures of anxiety and fear severity. There were few prominent differences between those who attributed their DRF to an MVA and those who reported some other reason for their fear. In addition, the data suggested useful preliminary subtypes of DRF that would benefit from further research attention. Study One then provided the impetus for Study Two, which entailed a more comprehensive investigation of the clinical characteristics and subtypes of DRF, as well as an examination of the role of driving skills in DRF. Study Two involved a quasi-experimental approach to the analysis of data from media-recruited driving-fearful and control groups each comprised of 50 participants. The control group was matched by average age and years of driving experience. All participants completed an initial questionnaire that provided demographic data as well as information about driving history and DRF. Various self-report measures of anxiety, fear, and avoidance behaviour were included in the initial questionnaire. Subsequently, those participants who met selection criteria underwent a diagnostic interview, further self-report questionnaires, and a practical driving assessment. Measures of self-rated and instructor-rated participant anxiety and driving skill were completed in conjunction with the driving assessment, mainly to ascertain the potential impact of test anxiety on the assessment results. Fearfuls were characterised by the reported severity of DRF when compared with controls. Helpseeking behaviour was not reflected in the relatively high levels of fear, anxiety, and avoidance behaviour reported by the fearful group. This was of particular concern given that almost half of the fearfuls met diagnostic criteria for at least one anxiety disorder. Social concerns (i.e., the perceptions of others) as a focus of fear were evident throughout the assessment, and fearfuls rated a higher likelihood of being involved in an MVA than controls, as well as higher levels of concern about the negative reactions of other drivers and injuring other people while driving. Subtypes of DRF were identified and will be an important focus for future research. In what is thought to be the first investigation of driving skills in DRF, the practical driving assessment found that fearfuls made more errors than controls. However, the pattern of errors was identical for both groups, indicating that fear and anxiety may affect the number rather than the type of errors made. The relationship between DRF and driving skills was discussed and then placed within the context of broader theories of driver behaviour. While the present research has served to further the understanding of DRFs and, in particular, has provided a starting point for understanding the role of driving skills in such fears, many avenues for future research are suggested. Additional studies will help to further clarify the findings of the present research, and to develop more clearly the kinds of practical and clinical recommendations that form the basis of efficient and effective treatment for DRF.
Keywords: Anxiety; Driving skills; Fields of Research::380000 Behavioural and Cognitive Sciences::380100 Psychology